Sexing European rabbits (Oryctolagus cuniculus), European brown hares (Lepus europaeus) and mountain hares (Lepus timidus) with ZFX and ZFY loci - Fontanesi, L.; Tazzoli, M.; Robinson, T. J.; Russo, V.; Pecchioli, Elena; Hauffe, Heidi Christine (Molecular Ecology Resources, 2008)
We describe a new method for the sex determination of tissue originating from Oryctolagus cuniculus (European rabbit), Lepus europaeus (European brown hare) and Lepus timidus (mountain hare) based on PCR-RFLP analysis of point mutations that differentiate the ZFX and ZFY gene sequences. Among several applications, this PCR-RFLP method could be used to investigate gender ratio and evaluate the population dynamics of these species using samples collected when sex cannot be identified.